Cedar Project: Conducting Health Research with Indigenous Peoples in a Good Way - Sharma, Richa; Bozoki, Violet; Henderson, Earl; Demerais, Lou; Christian, Kukpi7 Wayne; Pooyak, Sherri; Thomas, Vicky; Pearce, Margo; Jongbloed, Kate; Mazzuca, April; Spittal, Patricia (KULA, 2021)
The Cedar Project is an interdisciplinary, community-driven research project responding to the crises of HIV and Hepatitis C infection and contributing to the healing of young Indigenous people who use or have used drugs. We are a collective membership of Indigenous Elders, health/social service experts, researchers, and non-Indigenous allies. We situate our work in the context of strength, resilience, and rights to self-determination for Indigenous peoples while also acknowledging the ongoing impacts of historical, intergenerational, and current trauma, specifically those related to the child welfare systems. We provide epidemiological and qualitative evidence that reflects Indigenous perspectives of health and wellness. In this paper, we highlight over seventeen years of shared learnings on conducting research with Indigenous communities in a good way. Specifically, we elaborate on four key components of our unique project. First, our paradigm is to build on young Indigenous people's strengths while acknowledging grief and historical trauma. We recognize that Cedar participants are not statistics—they are relatives of Indigenous partners governing this study. Second, our processes are determined by Indigenous governance, led by Elders and rooted in cultural safety. Third, our research ethics are determined by terms of reference created by the Cedar Project Partnership and by embracing guidelines of TCPS and community-based research. Fourth, we are informed by multiple perspectives and research relationships between Elders, partners, students, academics, and research staff. Sharing our learnings with the larger research community can contribute to decolonizing research spaces by centering Indigenous knowledges and privileging Indigenous voice.